Phase I Study of Sorafenib Combined with Gemcitabine and Carboplatin in Patients with Advanced Solid Tumors - Daphne W. M. Voogd; Merel J. J. Lucassen; Ruud van der Noll; Sybrand W. J. Zielhuis; David Boss; Jos H. Beijnen; Hilde Rosing; Matthijs Tibben; Alwin D. R. Huitema; Jan H. M. Schellens; Neeltje Steeghs (Oncology and Therapy)
Abstract Introduction A combination of targeted anticancer drugs with cytotoxic therapy can potentially overcome multidrug resistance. The multi-target kinase inhibitor sorafenib demonstrates synergistic activity when combined with chemotherapeutics in preclinical models. This phase I trial aimed to assess safety, tolerability, efficacy, and pharmacokinetics of sorafenib with gemcitabine and carboplatin. Methods This single-center, open-label, dose-escalation and dose-expansion study included patients with advanced solid tumors considered for palliative treatment with gemcitabine and carboplatin. The maximum tolerated dose (MTD) was determined using a classic 3 + 3 dose-escalation design. Antitumor activity was evaluated every two treatment cycles. Results In total, 45 patients received treatment. Of the patients, 49% (n = 22) were male, and median age was 58 years [range: 27–72 years]. After dose-escalation, sorafenib 400 mg once daily (q.d.) on days 1−21, gemcitabine 500 mg/m2 on day 1 and day 8 (D1D8), and carboplatin AUC3 on day 1 (D1) every 3 weeks (Q3W) were established as the MTD. Grade 4 treatment-related toxicities, all hematological, were seen in 22% of the patients. Frequently observed grade 3 adverse events were neutropenia (33%), thrombocytopenia (31%), leukopenia (16%), and fatigue (13%). Dose reductions were required in 33% of the patients across all dose levels. Disease control rate after 18 weeks was 50%. Median progression-free survival and overall survival were 5.4 months and 10.1 months, respectively. Conclusions A recommended phase 2 regimen of sorafenib 400 mg q.d. combined with gemcitabine 500 mg/m2 D1D8 and carboplatin AUC3 D1, Q3W showed a manageable toxicity profile. This combination could provide an effective treatment option for patients in whom other therapies have failed since antitumor activity was seen across heavily pretreated tumor types. Alternative dosing regimens should be studied to optimize the dosing schedule. Trial Registration EudraCT: 2007-004129-75.